Influence of the Heating Rate on the Activation of Coal and Lignite Oxidation by Copper Nitrate; Coke and Chemistry; Vol. 63, iss. 8 - Larionov K. B. Kirill Borisovich; Mishakov I. V. Iljya Vladimirovich; Zenkov A. V. Andrey Viktorovich; Slusarskiy (Slyusarsky) K. V. Konstantin Vitalievich; Gromov A. A. Aleksandr Aleksandrovich (2020, 2020)
Title screen